HOW USER COMMENTS ON A NEWS SITE AFFECT PERCEPTIONS OF JOURNALISTIC QUALITY. AN EXPERIMENTAL STUDY USING STRUCTURAL EQUATION MODELING - Kümpel Anna Sophie; Springer, Nina (AoIR Selected Papers of Internet Research, 2015)
Researchers have just begun to study the effects of user comments on individual and public perceptions. Existing studies have shown distinct effects and indicate that comments can influence perceived media bias (Houston, Hansen, & Nisbett, 2011), inferences about public opinion (E.-J. Lee, 2012), impressions of political candidates (J. Lee & Lim, 2014) and even risk perceptions (Anderson, Brossard, Scheufele, Xenos, & Ladwig, 2014). Our goal is to look at a possible outcome that was not investigated yet— the influence on perceptions of journalistic quality. This offers an interesting field of study for two main reasons: First, if comments indeed affect quality perceptions, this has implications for media image and, more generally, trust in media outlets. Second, quality assessments also influence the (future) selection of media. As suggested by the Theory of Subjective Quality Assessment (TSQA, cf. Wolling, 2009), selection decisions are based on perceived features of the media product. Quality assessments can be one of the features that decide whether users are willing to give their attention to a certain media product—or ultimately refuse to do so.